Tinjauan Hukum tentang Penghapusan Buku Nikah di Kantor Wilayah Kementerian Agama Provinsi Papua - Siti Sahya Rauf; Zulfadli Zulfadli; Sugimin Sugimin (Jurnal Hukum dan Sosial Politik, 2025)
This study discusses the status of marriage books as legal and administrative documents, as well as the mechanism for their disposal as State-Owned Goods (BMN) at the Regional Office of the Ministry of Religious Affairs in Papua Province. The marriage book serves as valid evidence of marriage and plays an important role in population data management. As a document printed using the state budget (APBN), the marriage book is classified as BMN, and its management must comply with regulations. A qualitative approach with an empirical juridical method is used to examine the relationship between legal regulations and their implementation practices. Data were collected through interviews, observations, and literature studies with officials from the Islamic Guidance Division of the Ministry of Religious Affairs in Papua. The results indicate that the disposal of marriage books follows the Directorate General of Islamic Guidance Circular Letter No. 5 of 2024 and Ministry of Finance Regulation No. 83/PMK.06/2016. The disposal process is carried out in stages through administrative and physical mechanisms with principles of accountability and transparency. However, in Papua, the process of collecting unused marriage books has not yet reached the physical disposal stage. The disposal of marriage books is a strategic step in realizing good governance.